Communication—Co-Planar Structured Nano-Resistor Devices. (1st January 2019) - Kuo, Yue; Zhang, Shumao
Abstract : Nano-resistor devices made from the hard breakdown of co-planar MOS capacitors have been fabricated and studied. The complete device was made of a 2-mask, self-aligned process and IC compatible thin film materials. Broadband white light was emitted from the device upon the application of a gate voltage larger than the breakdown voltage due to the thermal excitation of the nano-resistors. Optical characteristics of the co-planar structured device are similar to those of the nano-resistor device prepared from the non-coplanar MOS capacitor. A large number of co-planar nano-resistor devices can be fabricated into an array form on the same substrate and individual devices can be operated without being interfered by adjacent devices.